Chlamydophila pneumoniae infection of the central nervous system in patients with multiple sclerosis. Issue 1 (5th January 2004) - Furrows, S J; Hartley, J C; Bell, J; Silver, N; Losseff, N; Stevenson, S; Chapman, M; Thompson, E J; Ridgway, G L; Giovannoni, G
Abstract : Background: Chlamydophila pneumoniae has been postulated as an aetiological agent in the pathophysiology of multiple sclerosis. Previous studies show conflicting results. Objective: To investigate patients with multiple sclerosis and other neurological diseases for evidence of past or present infection with C pneumoniae . Methods: 19 patients with multiple sclerosis and 29 with other neurological diseases were studied. Evidence was sought for past or present infection with C pneumoniae using polymerase chain reaction (PCR) and cell culture of cerebrospinal fluid (CSF), and enzyme linked immunosorbent assay and microimmunofluorescence of serum. Results: C pneumoniae was grown from the CSF of one patient with multiple sclerosis. PCR was negative in all cases. Anti-chlamydial antibodies were detected in the same proportion in each group. Conclusions: This study does not support the theory of an association between C pneumoniae and multiple sclerosis.